Function of Diction in Conveying the Meaning in Radio Drama: أحمد محمد محسن (Al-Academy, 2021)
Arabs knew the art of diction and elocution as part of their life in peace and war and in lamentation, satire, narration and description, as they were distinguished by influential and meaningful speeches in war and battle times, and the most prominent topics of the pre-Islamic rhetoric were pride, enthusiasm, bravery and other meanings related to heroism and call for war. It was not a long time when Arabs paid more attention to this great phonetic phenomenon, as they see that it elevates the status of the word and shows its meanings and significances. The current research aims to reveal the function of diction in conveying the meaning in radio drama. The research methodology: the researcher adopted the analytic descriptive method guided by the indicators driven from the theoretical framework, and due to the wide scope of the research community, the sample has been intentionally chosen from that community. The researcher analyzed the radio drama series (a journey in the days of the poet Mudhafar An-Nawab). The research has come up with the most important conclusions as follows:1- The concept of diction and rhetoric constituted a power which aims to convince individuals in their issues, which is listed by the Greek under the art of performance that has to be accompanied by diction through pronunciation, ringing bell, and melisma to constitute the audio picture in the spoken language.2- There are special rules in the science of diction, as diction is manifested through the speaker's speaking correctly where he can clarify his words and their meanings thus achieving the ultimate aim which is to influence the listening audience.